2021
DOI: 10.1002/trc2.12169
|View full text |Cite
|
Sign up to set email alerts
|

Change in modifiable dementia risk factors during COVID‐19 lockdown: The experience of over 50s in Tasmania, Australia

Abstract: Introduction Containment measures implemented to minimize the spread of coronavirus disease 2019 (COVID‐19) are reported to be negatively affecting mental health, diet, and alcohol consumption. These factors, as well as poor cardiometabolic health and insufficient physical and cognitive activity, are known to increase the risk of developing dementia. COVID‐19 “lockdown” measures may have exacerbated these dementia risk factors among people in mid‐to‐later life. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…The majority of studies noted a significant reduction in PA during the Covid-19 lockdown ( n = 32). In contrast, only few studies found an increase in PA ( n = 5) [ 57 , 72 , 84 , 100 , 109 ] while six studies failed to detect any changes in PA [ 50 , 51 , 68 , 71 , 86 , 99 ]. Fourteen other studies showed both, a decrease and an increase in PA, depending on the PA characteristics under study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of studies noted a significant reduction in PA during the Covid-19 lockdown ( n = 32). In contrast, only few studies found an increase in PA ( n = 5) [ 57 , 72 , 84 , 100 , 109 ] while six studies failed to detect any changes in PA [ 50 , 51 , 68 , 71 , 86 , 99 ]. Fourteen other studies showed both, a decrease and an increase in PA, depending on the PA characteristics under study.…”
Section: Resultsmentioning
confidence: 99%
“…The four studies with participants from age groups 2 and 3 (20 to over 65 years) included a total of 24,066 (11,561 female) participants with a mean age between 51.6 years [ 106 ] and 63.4 years [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations